Analisis Kemampuan Koneksi Matematis Siswa dalam Menyelesaikan Soal Cerita Matematika - Syatia Perwira Darmawansyah; Syahrul Azmi; Wahidaturrahmi Wahidaturrahmi; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research aims to find out and describe the level of ability of mathematical connections of students in solving math story problems in class VIII at State Junior High School 2 Labuapi school year 2021/2022. This research is descriptive quantitative research. Sampling techniques using purposive sampling techniques and the research subjects selected in this study were 10 students of class VIII of State Junior High School 2 Labuapi. Data collection techniques using tests and interviews. Data analysis techniques are carried out using the data reduction stage, the data presentation stage, and the conclusion withdrawal stage. Overall, students who are in the category are very good as many as 2 people, good categories as many as 3 people, enough categories as many as 2 people, categories less as much as 2, and categories are less than as many as 1 people. In general, it is seen from the average student grades that the ability of students' mathematical connections in solving math story problems is in the category of sufficient. Students in the category are very good and good already able to master both indicators of mathematical connections, students in the category are quite only able to master one of the mathematical indicators only, students in the category are less able to master both indicators of mathematical connections, and students in the category are very less able to master both mathematical indicators.